Using The Cancer Genome Atlas as an Inquiry Tool in the Undergraduate Classroom - Hankey, William; Zanghi, Nicholas; Crow, Mackenzie M.; Dow, Whitney H.; Kratz, Austin; Robinson, Ashley M.; Robinson, Meaghan R.; Segarra, Verónica A. (Frontiers in Genetics, 2020)
Undergraduate students in the biomedical sciences are often interested in future health-focused careers. This presents opportunities for instructors in genetics, molecular biology and cancer biology to capture their attention using lab experiences built around clinically relevant data. As biomedical science in general becomes increasingly dependent on high-throughput data, well-established scientific databases such as TCGA have become publicly available tools for medically relevant inquiry. The best feature of this database is that it bridges the molecular features of cancer to human clinical outcomes, allowing students to see a direct connection between the molecular sciences and their future professions. We have developed and tested a learning module that leverages the power of TCGA datasets to engage students to use the data to generate and test hypotheses and to apply statistical tests to evaluate significance.